Stocking the shop: Nineteenth-Century flower buying - DelPrince, James (Journal of Floriculture and Landscaping, 2020)
In the third quarter of the 19th century, urban florists purchased a wide variety of cut flowers for resale. Roses and carnations were staples, and the season dictated market availability. In London, the expansion of Covent Garden in 1870 facilitated the importation of flowers from all over Europe. New York florists began to purchase flowers through wholesalers who carried stock grown in state and nearby, which was transported by train to the city and distributed to approximately 200 florist shops at the turn of the 20th century.